2006
DOI: 10.1007/s10664-006-9007-3
|View full text |Cite
|
Sign up to set email alerts
|

A study of effectiveness of dynamic slicing in locating real faults

Abstract: Dynamic slicing algorithms have been considered to aid in debugging for many years. However, as far as we know, no detailed studies on evaluating the benefits of using dynamic slicing for locating real faults present in programs have been carried out. In this paper we study the effectiveness of fault location using dynamic slicing for a set of real bugs reported in some widely used software programs. Our results show that of the 19 faults studied, 12 faults were captured by data slices, 7 required the use of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…Thus, SFL using BS adopts stronger semantics to evaluate the correlation between statements and failures compared to SFL using code coverage. In addition, it has been demonstrated that BS is effective to capture the influence of the execution of a statement on the output and can locate a wide spectrum of faults [13], that is, BS is generally and strongly correlated with the output of a test case. That is the reason why SFL using BS shows the highest fault localization effectiveness among the four SFL techniques.…”
Section: • Er1: Sfl(fcandbs)mentioning
confidence: 99%
“…Thus, SFL using BS adopts stronger semantics to evaluate the correlation between statements and failures compared to SFL using code coverage. In addition, it has been demonstrated that BS is effective to capture the influence of the execution of a statement on the output and can locate a wide spectrum of faults [13], that is, BS is generally and strongly correlated with the output of a test case. That is the reason why SFL using BS shows the highest fault localization effectiveness among the four SFL techniques.…”
Section: • Er1: Sfl(fcandbs)mentioning
confidence: 99%
“…In contrast, most later work on dynamic slicing 'defines' dynamic slicing based on the algorithms used to compute it (e.g., Agrawal et al [1] and Demillo et al [16]). Although many research prototypes and approaches exist [2], [6], [7], [36], [42], [53], [54], all approaches are for a single specific programming language whereas the observation based nature of ORBS allows it to slice programs distracted from multiple programming languages [10].…”
Section: Rq3: Observational Sensitivity To Inadequate Testingmentioning
confidence: 99%
“…It has been shown that dynamic program slicing [1,16] can help discover faults [28], but the computational effort is enormous. We have not yet investigated the possible performance gains (reduction of complexity) made possible by the special setting of unit testing, but expect that it will make it more tractable.…”
Section: Related Workmentioning
confidence: 99%